Discourses of Exclusion: Immigrant-Origin Youth Responses to Immigration Debates in an Election Year. Issue 1 (2nd January 2017) - Dabach, Dafney Blanca; Fones, Aliza; Merchant, Natasha Hakimali; Kim, Mee Joo
ABSTRACT: Political discourse on immigration policy often provides a window into a society's boundaries of inclusion and exclusion. Here, we seek to understand how those in liminal positions respond to political debates that raise issues of boundary maintenance. Drawing from Bakhtinian concepts of authoritative and internally persuasive discourses as well as Gramsci's concept of common sense, we analyzed how a superdiverse sample of 26 immigrant-origin adolescents (from Asia, Latin America, Africa, and Europe) responded to video segments of presidential debates from the 2012 U.S. election. Youth's responses to presidential video clips about undocumented immigration policies fell along a spectrum from inclusionary to exclusionary, with many voicing mixed responses to immigration policies. Half of the youth referenced their own family's migration experience when discussing immigration policy, most frequently in empathetic ways; however, this did not preclude them from aligning with discourses of exclusion. The theme of fairness was prevalent in their responses, yet it emerged in distinct ways. This work highlights the need to interrogate common-sense discourses of exclusion.